The Role of Al-Kawniyyat Verses in The Glorious Qur’an On Contemplation and Scientific Discoveries: The Neglected Treasures - Kitota, Abdillah Mussa (Journal of Quranic Sciences and Research, 2023)
Despite the fact thatthe Qur’an, 16:89 has described the Qur’an as a book which clarifies everything, available evidence suggests that most Muslims have neglected the most important treasures of al-ayat al-kawniyyat [verses related to creation] as tools for both contemplation and scientific discoveries. This study has adopted aqualitative systematic review design to analyze these treasures. The relevant data were collected from the Qur’an, published reports and articles, and analyzed by thematic approach. The results show that the Qur’an contains many kawniyyat verses that in addition to laying-down the foundation for contemplation of the wonders and majesty of Allah (S.W.T) in His creation, they also direct us how to understand and applying them for scientific and technological discoveries. This study is offered as a modest attempt to stimulate our psychological motivation with a view to enhancing and enriching our understanding on how to deal with kawniyyat verses.